2012
DOI: 10.1088/0953-2048/25/12/125004
|View full text |Cite
|
Sign up to set email alerts
|

Interferometer measurements of terahertz waves from Bi2Sr2CaCu2O8+dmesas

Abstract: We fabricated rectangular mesa structures of superconducting Bi 2 Sr 2 CaCu 2 O 8+d (Bi2212) using e-beam lithography and Ar ion beam etching techniques for terahertz (THz) emission. c-axis resistance versus temperature (R-T), current-voltage (I-V) characteristics and bolometric THz power measurements were performed to characterize Bi2212 mesas. The emission frequency of mesas was determined using a Michelson interferometer setup which also demonstrates polarized emission. Interference patterns of THz radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The goal is to fill the so-called "THz gap" [21] with the intrinsic Josephson junctions (IJJs) stacked one-dimensionally along the c axis of a single crystal [19,20,22,23]. Since there are N ∼ 670 identical IJJs in a single-crystalline Bi2212 mesa 1 μm thick, the coherent output power P ∝ N 2 from a mesa can be enhanced from ∼pW for a single junction to tens of μW [19,20,[24][25][26][27][28]. However, Bi2212 mesa structures with N > 10 3 IJJs encounter serious heating problems due to the large I injected into the mesa [19], causing the mesa to develop a hot spot T (r) that exceeds T c on its top surface, even though the bath temperature T bath of its substrate is held to well below T c [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to fill the so-called "THz gap" [21] with the intrinsic Josephson junctions (IJJs) stacked one-dimensionally along the c axis of a single crystal [19,20,22,23]. Since there are N ∼ 670 identical IJJs in a single-crystalline Bi2212 mesa 1 μm thick, the coherent output power P ∝ N 2 from a mesa can be enhanced from ∼pW for a single junction to tens of μW [19,20,[24][25][26][27][28]. However, Bi2212 mesa structures with N > 10 3 IJJs encounter serious heating problems due to the large I injected into the mesa [19], causing the mesa to develop a hot spot T (r) that exceeds T c on its top surface, even though the bath temperature T bath of its substrate is held to well below T c [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many different adhesive materials were used to transfer superconducting crystals on substrate such as silver epoxy (Turkoglu et al 2012;Koseoglu et al 2011), polyimide and non-photosensitive polyimide PIX (Yamada et al 2007;You et al 2005;Wang et al 2001;Yamaki et al 2011). The preference of adhesive can affects response time of bolometer, and the chosen epoxy has to be compatible with temperature cycling.…”
Section: Methodsmentioning
confidence: 99%
“…In more recent times, progress in the development of THz sources in our group (Demirhan et al 2015;Turkoglu et al 2013Turkoglu et al , 2012 and pioneering efforts in the production of THz detectors have been observed. For detecting weak signals in the submillimeter or in some other words terahertz range, there exists a promising contestant namely superconducting Hot Electron Bolometers (HEBs).…”
Section: Introductionmentioning
confidence: 99%
“…While there is a high motivation to perform experiments in the THz frequency range, new sources, detectors and optical components are still needed. Recently, there have been many improvements in the development of THz sources (Turkoglu et al 2012(Turkoglu et al , 2013Wang et al 2009) and in the fabrication of THz detectors (Rice et al 1994;Hu and Richards 1989;Du et al 2008).…”
Section: Introductionmentioning
confidence: 99%